Natural outcrossing in Stylosanthes capitata - Miles, John W. (1983)
Plant-to-plant phenotypic variation has been observed within accessions of S. capitata maintained at the Centro Internacional de Agricultura Tropical (CIAT) since shortly following introduction. A small experiment was conducted to determine the potential importance of natural outcrossing as a cause of such variation. Plants of contrasting phenotypes (hairy or non-hairy stipules) were transplanted in close proximity in a field plot. Outcrosses among the open-pollinated progeny of non-hairy plants were identified by the presence of stipule hairs. Overall, 19.5% of 2097 open-pollinated progeny were classed as outcrosses. The implications of this finding in terms of S. capitata germplasm collection and maintenance, seed production, and breeding methods are discussed.